2020
DOI: 10.1007/s11665-020-04913-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Microhardness Analysis of Metastable Beta Titanium Alloy Ti-15V-3Cr-3Al-3Sn Consolidated Using Equal-Channel Angular Pressing from Machining Chips

Abstract: Solid consolidation recycling of metastable beta titanium alloy Ti-15V-3Cr-3Al-3Sn from machining chips by using back pressure assisted equal channel angular pressing (BP-ECAP) under different processing conditions were carried out. Nearfully dense specimens could be achieved after multiple passes at 500 °C with the aid of back pressures. Microstructure analysis by SEM and TEM shows that ultrafine equiaxed α grains (~180 nm) formed in the β matrix homogeneously as a result of extensive dislocations, vacancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…1. Ti 15 V 3 Cr 3 Sn 3 Al HEAs are employed as embedded aircraft equipment with their exceptional strength ratio and outstanding cold formability [231]. Ti 3 Al 8 V 6 Cr 4 Zr 4 Mo, on the other hand, has a foothold in the aviation sector since of a combination of properties including high cycle fatigue high strength, and plasticity, high cycle fatigue maintainability, and outstanding fracture toughness [232].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…1. Ti 15 V 3 Cr 3 Sn 3 Al HEAs are employed as embedded aircraft equipment with their exceptional strength ratio and outstanding cold formability [231]. Ti 3 Al 8 V 6 Cr 4 Zr 4 Mo, on the other hand, has a foothold in the aviation sector since of a combination of properties including high cycle fatigue high strength, and plasticity, high cycle fatigue maintainability, and outstanding fracture toughness [232].…”
Section: Potential Applicationsmentioning
confidence: 99%
“…In the study of the α phase, it was found that the high dislocation density and a large number of non-equilibrium grain boundaries/sub-grain boundaries generated during the ECAP process, which provide a good nucleation site for α-phase precipitation, and the ultrafine equiaxed α grains were formed in the β matrix. Moreover, vacancies and non-equilibrium grain boundaries in the microstructure enhance atomic diffusivity and accelerate the formation of the α-phase [111]. Dyakonov et al argued that the evolution of the primary α phase was driven by continuous dynamic recrystallization [112].…”
Section: Phase 231 Titanium Alloysmentioning
confidence: 99%
“…Yaşlandırma süreci, bu alaşımların mukavemetinde % 50-80 artış sağlamaktadır. Bu alaşımlar içerisinde Amerikan Hava Kuvvetleri'nin desteğiyle geliştirilen Ti-15V-3Cr-3AI-3Sn (Ti-15-3) alaşımı, özellikle havacılık endüstrisinde geniş kullanım alanlarına sahip yarı kararlı titanyum alaşımlarındandır [45], [46]. Literatür araştırmasında çalışmaların, ısıl işlemlerin sonucunda alaşımın mekanik özelliklerinin gelişimine yönelik odaklanıldığı görülmüştür.…”
Section: Fazi çAlişmalariunclassified